International postgraduate student satisfaction towards staff service in UUM - Syazwani, Muhammad Raffi Shah Liew (2018)
Student satisfaction has become a significant factor in today’s competitive environment for higher education. The reason of this statement because of satisfied students could help higher education to retain existing students and attract new students. The researcher was interest to make this study due to the declining number of international postgraduate students in UUM. The objective of this study was to determine the international postgraduate student satisfaction towards staff service in UUM in term of responsiveness, reliability, and courtesy of the staff. The data collection process was used the survey method which utilized the questionnaire. The data analysis has used SPSS version 20 to analyze the Pearson Correlation and Multiple Regression of the study. There were 226 questionnaires has been distributed. The main finding of this study showed that there were significant relationships between responsiveness, reliability, and courtesy with student satisfaction.